Mathematical modelling and optimization of parameters for Al-Si-Fe aluminum alloy reinforced by Al2O3 and graphite particles using Taguchi method. (2021) - Daba, Robale Dinsa; Sinha, Devendra Kumar; Beri, Habtamu; Gautam, Satyam Shivam; Mohammed Sayeed Ahmed, Gulam; Sewak Singh, Ram
Abstract: In the present scenario the aluminum and its alloys are preferred due to requirement of lightweight high strength material. The present research article interrogates experimentally the study of actual density and porosity using powder metallurgy method. The experimental design is done using Taguchi L16 orthogonal array. Actual density and porosity has been analyzed based on 'smaller is best' basis. Actual density and porosity are calculated using Archimedes principle. The leverage of four levels and five process parameters such as weight percentage of Al2 O3, weight percentage of graphite, compaction pressure, compaction time and milling time are considered. Results reveal that Al2 O3 weight percentage has the highest leverage on density followed by compaction time and graphite weight percentage.